A frailty-contagion model for multi-site hourly precipitation driven by atmospheric covariates. (April 2015) - Koch, Erwan; Naveau, Philippe
Highlights: We model multi-site precipitation variability by common atmospheric factors. Our model is hourly and accounts for the dependence between occurrence and intensity. This model generates accurately both dry episodes and heavy rainfall. Our application focuses on hourly precipitation in Brittany over 1995–2011. Abstract: Accurate stochastic simulations of hourly precipitation are needed for impact studies at local spatial scales. Statistically, hourly precipitation data represent a difficult challenge. They are non-negative, skewed, heavy tailed, contain a lot of zeros (dry hours) and they have complex temporal structures (e.g., long persistence of dry episodes). Inspired by frailty-contagion approaches used in finance and insurance, we propose a multi-site precipitation simulator that, given appropriate regional atmospheric variables, can simultaneously handle dry events and heavy rainfall periods. One advantage of our model is its conceptual simplicity in its dynamical structure. In particular, the temporal variability is represented by a common factor based on a few classical atmospheric covariates like temperatures, pressures and others. Our inference approach is tested on simulated data and applied on measurements made in the northern part of French Brittany.